Model Promosi Kesehatan di Tempat Kerja Multilevel: Bagaimana Implementasinya dalam Mengubah Perilaku Pekerja? (Suatu Kajian Kepustakaan) - Zahtamal .; Wasilah Rochmah; Yayi Suryo Prabandari; Lientje K Setyawati (Jurnal Kesehatan Komunitas, 2015)
The consequences of the diseases that are often occured on workers is a huge loss for the company and the workers. In order to overcome the problem of disease, workplace health promotion (WHP) efforts are needed, in particular to change the workers behavior. The application of behavioral change in the workplace are more complex. Changes in behavior are not just driven by individual factors, but also by the role of external factors, so that the targeted WHP is a multilevel basis. This article describes the formula WHP multilevel models that can be applied to change unhealthy worker behavior. The selection model of behavior change should be considered in the formulation of a multilevel WHP. It is used as a reference to modify the behavior that will be addressed. Furthermore, the principle of selecting strategies and behavior change methods, tailored to the target level of intervention. Overall, these principles are formulated in a comprehensive reference WHP program and implemented effectively and efficiently in the workplace. This article can be a reference for those who will implement WHP with behavioral changes in a multilevel approach.